ESTIMATION THE SIZE OF UNDERGROUND ECONOMY AND TAX POTENTIAL LOSS IN INDONESIA FROM 2000 – 2017 - Ramadhan, Fairuz Muhammad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
Gross Domestic Product (GDP), is often considered the best measure of how well the economy is working. However, the weakness of GDP is that it does not include the underground economy in its calculations. This study attempts to measure the size of the underground economy and tax potential loss in Indonesia by using currency demand approach (CDA) method from 2000 to 2017, also to see how effective the tax amnesty policy in reducing the underground economy activity and tax potential loss in Indonesia. The average size of the underground economy in Indonesia from 2000 to 2017 is around IDR 528 trillion or 7,58 percent of GDP annually. While the average tax potential loss obtained from the underground economy activity is IDR 56,23 trillion per year or 0,95 percent of GDP. The results of tax amnesty policy implementation showed a decrease in the magnitude of the underground economy activity and tax potential loss, a decline of 4 percent in the underground economy activity in 2016-2017 and a decrease of 8 percent in tax potential loss in 2016 and 3 percent in 2017.Keywords: GDP, underground economy, tax potential loss, tax amnesty policy, currency demand approach